Formulation of PVA and PEG hydrogel via Freeze-Thaw method - Ahmed, Afnan Shihab; Bakhtiar, M. Taher; Mandal, Uttam Kumar; Md. Jaffri, Juliana (2015)
The Hydrogels are three dimensional, water swollen structure composed of mainly hydrophilic homopolymers or copolymers like polyvinyl alcohol (PVA), Poly ethylene glycol (PEG) etc., utilized as a part of various biomedical fields, and are as yet producing for new encouraging applications. Physically cross-linked synthetic polymers, PVA and PEG, hydrogels are excellent materials owing to their biological tissue like nature. Transparent PVA and PEG hydrogels with varying polymer concentrations were obtained by using freeze-thaw method.gel fraction and swelling behavior were investigated. PVA (Mw 195,000, Sigma-Aldrich), PEG 400 (Merck) hydrogels prepared by dissolving PVA in deionized water with concentrations (6%, 8%, and 10%), PEG with concentrations (1%, 3%, and 5%) were added and the gel were autoclaved at 121°C for 15min. The clear solution was poured into a Petri dish to undergo four consecutive cycles of 16 h freezing at -80°C and 8 h thawing at RT. Gel properties such as gel fraction, swelling index, water vapour transmission rate and mechanical strength were investigated. Four consecutive cycles of freezing and thawing formed an insoluble and entangled hydrogel. Present study demonstrates a systematic variation in physico-chemical properties of the developed using the freezing–thawing method with PVA and PEG as a function of polymer concentration. From the results with increasing PVA there is an increase in the gel fraction while increasing PEG concentration decreased gel fraction. However, increasing PVA decreased the swelling, and by adding PEG increases the swelling ratio and the water vapour transmission rate. The developed hydrogel using the freezing–thawing method with PVA and PEG was more swellable and flexible.